Acute coronary syndrome and renal dysfunction - F. I. Belyalov (Столичная издательская компания, 2016)
Renal dysfunction in patients with acute coronary syndrome complicates the diagnosis, worsens the short- and long-term prognosis, reduces the effectiveness of the reperfusion therapy, and increases the risk of bleeding. It is important to aim for treatment based on the evidence-based studies and according to the updated guidelines of the professional associations.